2020
DOI: 10.25259/jcis_58_2020
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Chest Computed Tomography in Asymptomatic Patients of Positive Coronavirus Disease 2019: A Case and Literature Review

Abstract: Coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is an ongoing global health emergency. At present, patients are the primary source of infection. A randomly diagnosed confirmed case of COVID-19 highlights the importance of computerized tomography of thorax in diagnosing asymptomatic patients. In the early phase of COVID-19, routine screenings miss patients who are virus carriers, and tracking travel history is of paramount importance to early detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Patients are undergoing routine CT examinations for non-COVID-19 related reasons. For example, CT examinations may be conducted for routine cancer screening, monitoring for elective surgical procedures ( 8 ), and neurological examinations ( 9 ). Since such CT examinations are being conducted as a routine procedure regardless of COVID-19, there are no additional cost or resource constraints associated with leveraging such examinations for COVID-19 screening as well.…”
Section: Introductionmentioning
confidence: 99%
“…Patients are undergoing routine CT examinations for non-COVID-19 related reasons. For example, CT examinations may be conducted for routine cancer screening, monitoring for elective surgical procedures ( 8 ), and neurological examinations ( 9 ). Since such CT examinations are being conducted as a routine procedure regardless of COVID-19, there are no additional cost or resource constraints associated with leveraging such examinations for COVID-19 screening as well.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical institutes around the world have explored the use of computed tomography (CT) imaging as an effective, complementary screening tool alongside RT-PCR ( 2 , 5 , 6 ). In particular, studies have shown CT to have great utility in detecting COVID-19 infections during routine CT examinations for non-COVID-19 related reasons such as elective surgical procedure monitoring and neurological examinations ( 7 , 8 ). Other scenarios where CT imaging has been leveraged include cases where patients have worsening respiratory complications, as well as cases where patients with negative RT-PCR test results are suspected to be COVID-19 positive due to other factors.…”
Section: Introductionmentioning
confidence: 99%
“…The severity grading is based on any opacication of lung parenchyma including (8) ground glass opacities, consolidation . We speculate that this relatively uncomplicated method could provide objective means to speed up the identication of patients with severe disease, especially in conditions of meager availability of healthcare resources and to ( 9,10).…”
Section: Discussionmentioning
confidence: 99%